2013
DOI: 10.1016/j.neuroimage.2013.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Controlling automatic imitative tendencies: Interactions between mirror neuron and cognitive control systems

Abstract: Humans have an automatic tendency to imitate others. Although several regions commonly observed in social tasks have been shown to be involved in imitation control, there is little work exploring how these regions interact with one another. We used fMRI and dynamic causal modeling to identify imitation-specific control mechanisms and examine functional interactions between regions. Participants performed a pre-specified action (lifting their index or middle finger) in response to videos depicting the same two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 96 publications
(161 reference statements)
7
87
1
5
Order By: Relevance
“…Thus, the posterior part of the inferior frontal gyrus seems to be activated when participants attended to the biological characters (humanlike appearance) of the pseudo-postures, but might be normally under inhibitory control. One of the most promising brain regions, which pertain to the inhibitory control of motoric embodiment, is the prefrontal cortex, i.e., the anterior part of inferior frontal gyrus [10] [16] and/or anterior insula [19]. This prefrontal control network could suppress the MNS activity in response to the degree of the configural similarity between observed objects and human body postures stored as conceptual knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the posterior part of the inferior frontal gyrus seems to be activated when participants attended to the biological characters (humanlike appearance) of the pseudo-postures, but might be normally under inhibitory control. One of the most promising brain regions, which pertain to the inhibitory control of motoric embodiment, is the prefrontal cortex, i.e., the anterior part of inferior frontal gyrus [10] [16] and/or anterior insula [19]. This prefrontal control network could suppress the MNS activity in response to the degree of the configural similarity between observed objects and human body postures stored as conceptual knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the occipital region, we found significant main effects of the ease of picture-naming in channels 13, 15, 20, 21, and 24 (F(1, 13) = 6.00, p < 0.05; F(1, 13) = 6.37, p < 0.05; F(1, 13) = 5.99, p < 0.05; F(1, 13) = 4.87, p < 0.05; F(1, 13) = 9.63, p < 0.01, respectively), and significant interactions between the picture-naming condition and period in channels 13,15,16,20,22,23, and 24 (F(10, 130) = 2.09, p < 0.05; F(10, 130) = 2.25, p < 0.05; F(10, 130) = 2.34, p < 0.05; F(10, 130) = 2.00, p < 0.05; F(10, 130) = 2.07, p < 0.05; F(10, 130) = 3.00, p < 0.01; F(10, 130) = 3.46, p < 0.01, respectively). Post-hoc comparisons using Shaffer's modified Bonferroni correction revealed that these interactions were due to the large responses under the easy condition as compared to those under the difficult condition during the period from target-presentation to confidence-judgment (p < 0.05).…”
Section: Nirs Data In the Novel Contour Shape Conditionmentioning
confidence: 95%
See 3 more Smart Citations